Rancang Bangun Sistem Informasi Monitoring Dan Evaluasi Kinerja Mesin Pada Pkis Sekar Tanjung - Santoso, Arif Budiman; Sunarto, M. J. Dewiyani; Setyawan, Henry Bambang (Jurnal JSIKA, 2013)
Abstract: in a effort to raise it’s production capacity of PKIS Sekar Tanjung should have information about the performance machine. Information to date is not yet available due to the limited recording data that has not been adequate. As result, the information generated is not able to monitor and evaluate the performance each machine, and cann’t be seen directly by the manager. PKIS Sekar Tanjung requires systems to assist managers in dealing with the problems of engine performance. Therefore, a single information system, monitoring and evaluation of the performance machine. In calculating the performance each machine uses a method of Capacity Utilization Time & Efficiency (CUTE) whose data from logsheet. This resulted in report the evaluation the performance each machine, report output product each machine, and report problem each machine. With this information system monitoring and evaluation of performance machine, manager is easy to track and in evaluate each machine. This system in monitor performance each machine that form of charts and table that could be drilldown to the more specific level. Thus manager can identify problems machine precisely and more direted. Keywords: Kinerja Mesin, Sistem Informasi, Monitoring, Evaluasi, CUTE